An experimental study in rabbits to determine the role of estrogen in reducing joint degeneration . abstract (Journal of Hama University, 2024)
Joint degeneration is one of the most common disorders of the musculoskeletal system, which is characterized by gradual damage to cartilage, osteoblast genesis, and subchondral bone, which causes joint pain and limitation of movement with deformity and motor disability, which hinders daily activity, in addition to the high cost in terms of therapeutic intervention. Because of the chronic course of the disease. Gender and hormonal status were included among several factors as risk factors for joint degeneration. The experiment was conducted on 20 physically and sexually mature female rabbits and divided into two groups: healthy females and females who underwent surgical removal of their ovaries and uterus. This research showed, for the first time, a negative effect of a decline in estrogen on blood calcium concentration. The results of this study also showed, through macroscopic anatomy of the knee joint, the presence of joint damage as signs of joint degeneration in comparison between the two groups, and it is associated with a decrease in estrogen concentration.